Pemenuhan Penilaian Aspek Transaksi Berjaminan Dalam Business Ready (B-READY) Sebagai Upaya Perbaikan Iklim Investasi Indonesia - Dwi Ayu Rarasmitha (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
To improve the investment climate and increase foreign investment, the Government can make policies that refer to international standard parameters. Business Ready (B-READY) is a parameter to measure investment and business climate that can be used by investors to determine the host country. One of the things assessed in B-READY is related to aspects of secured transactions as part of the assessment of the financial services sector. Access to finance is one of the important things in the sustainability of a business. Secured transactions are one of the instruments commonly used in providing financing. With the juridical normative method, this paper will emphasize the use of secondary data related to the B-READY assessment methodology and laws and regulations related to secured transactions in Indonesia. Based on the analysis carried out, it is found that there is a fragmentation of regulations related to secured transactions, which is not in line with the assessment of indicators on B-READY that require an integrated regulatory framework regarding secured transactions. This paper considers that it is necessary for the regulatory framework related to secured transactions to adopt the assessment indicators on aspects of secured transactions in the B-READY parameter.